Accruing individual potential for creativity and innovation in biotechnology firms. (1st January 2012) - Raqshin, Samar; Nirjar, Abhishek
India has shown a noteworthy growth in its high technology sector during last two decades. High-tech enterprises are known by their knowledge-based environment driven by creativity and innovations. The creative behaviour of an individual is influenced both by cognitive and non-cognitive factors of personality, and an inter-relationship exists between individual and organisational variables of creativity. The present paper concentrates on examining the role of positive psychological capital ('PsyCap': constituting self-efficacy, hope, optimism and resilience) on enhancing the individual potential for innovation. The paper is exploratory in nature and focuses on the biotechnology sector in India through three case studies. It is revealed that the psychological construct 'PsyCap' can be effectively utilised for enhancing an individual's potential for innovation.